The HIV and AIDS academic curriculum in Higher Education - de Lange, Naydene (South African Journal of Higher Education, 2016)
While a university’s core business of teaching, research and engagement is underpinned by national and global imperatives, the purpose of the university is embedded in its students’ realities of living, learning and working in the world. A key challenge for all academics, therefore, is to keep their academic project, whether in engineering or health sciences, ‘embedded in the students’, while at the same time, preparing them for work in the world. The purpose of this paper is to argue that the university academic curriculum should be harnessed more vigorously to address HIV and AIDS – a reality impacting the student corps. This is achieved by pointing to higher education policy on integrating HIV and AIDS into the academic curriculum; by showing how ‘champions’ across various disciplines in the higher education sector are already integrating HIV and AIDS in the curriculum; by drawing on a pilot study in the education sector to raise possibilities for integration; and finally, by positing some provocative propositions towards a more intensive integration of HIV and AIDS into the higher education academic curriculum. This paper, therefore, seeks to persuade, but also to ensure, that the work of the higher education institution remains ‘embedded in its students’, and that the curriculum is responsive and engaged, and contributes to the public good of South African society as a whole.